Kajian Tahap Kepentingan Kriteria Bangunan Hijau Terhadap Nilai Harta Tanah Kediaman Melalui Kaedah Analytical Hierarchy Process (AHP) - Abd Hamid, Saedah Napisah; Mohd Safian, Edie Ezwan (Research in Management of Technology and Business, 2020)
Green buildings are often seen as an inner initiative for sustainable development. There are various applications of green technology used in buildings regardless of the type of property such as commercial, industry, and residential. Nowadays, various green technology criteria have emerged where it is influenced by current demand as well as technological developments. However, studies involving green technology and its importance in influencing the value of the property are very less especially in the Johor Bahru area. Therefore, this study was conducted is to identify the green building criteria and their level of importance in effect the value of residential-type properties (apartments) around Johor Bahru. A total of 20 respondents consisting of real estate players were involved in this study. Descriptive Analysis and Analytical Hierarchy Process (AHP) has been used in achieving the objectives of the study. The result shows energy efficiency has obtained the highest importance specifically weighting of 17.6% followed by water efficiency by 17.1%, quality of indoor environment and innovation by 16.6% each, resources and materials by 16.4%, and sustainable site management and planning by 15.8%. The results of these findings are expected to open the eyes of real estate market players in making decisions whether for investment or business purposes in order to improve the real estate market performance, especially residential type in Johor Bahru, Malaysia.